Fungsi Akta De Command dalam Proses Lelang Jaminan Debitur Menurut Peraturan Perundang-undangan di Indonesia - Dede Iskandar; Taufik Yahya; Helmi Helmi (Jurnal Ilmiah Dikdaya, 2023)
The Notaries are charged with great responsibility for every action taken, in this case making an authentic deed. The world of auctions is known for the acte de command. The temporary purchase plan by the bank must begin with the creation of an authentic deed known as the Deed of Purchase for Others or also known as the Acte de command which essentially contains a statement that the creditor bank will participate in the auction to purchase its credit collateral assets. Acte de command has an important role for banks that have auctioned off their auctioned collateral. The auction is carried out in the context of paying off bad loans by debtors. In practice, there are banks that use Acte de command in situations where there are several other bidders who are interested in buying the bank's collateral. takeover of collateral through an auction by signing an agreement to take over the collateral between the bank and the debtor or making a notarial report of credit settlement, then proceed with making an Acte de Command, which is a statement between the buyer appointed by the bank (usually a bank employee) and the debtor which states that the buyer is acting buying collateral is done for the benefit of another party whose name will be determined at a later date who is appointed to replace the buyer. The legal issue in this thesis is the obscurity of norms, because not all banks in Indonesia use de command deed for the auction process. Collateral goods purchased must be sold no later than 1 (one) year. If the parties to the deed are in default, then proceed with the court process and the goods guaranteed will be auctioned, and if the maximum time limit for the de command expires, the deed will be canceled or forfeited